Astronomische biografieën - Baneke, David (Studium, 2019)
This essay review discusses four biographies of Dutch astronomers:  Kapteyn, Oort, De Sitter, and Fockens. The first three are established names from twentieth century astronomy, the fourth is a forgotten, nineteenth-century talent, whose career never got off the ground. Three of the books were written by ‘amateur’ historians. I shall argue that professional historians should appreciate this group, and their efforts, for what they initiate rather than criticize them for what they omit.